Investigating a Mobility-Aware QoS Model for Multimedia Streaming Rate Adaptation. (1st October 2015) - Sardis, Fragkiskos; Mapp, Glenford; Loo, Jonathan; Aiash, Mahdi; Vinel, Alexey
Abstract : Supporting high quality multimedia streaming on wireless devices poses several challenges compared to wired networks due to the high variance in network performance encountered in the mobile environment. Although rate adaptation is commonly used in multimedia applications to compensate for fluctuations in network performance, it is a reactive mechanism which is not aware of the frequently changing connectivity that may occur on mobile devices. This paper proposed a performance evaluation model for multimedia streaming applications that is aware of user mobility and network performance. We presented an example of mathematical solution to the model and demonstrated the functionality using common mobility and connectivity examples that may be found in an urban environment. The proposed model is evaluated based on this functionality and how it may be used to enhance application performance.